A Ranking of the Support Criteria for Employees' Productivity Improvement When Working from Home - Soenandi, Iwan Aang; Saint Witerang, Leander (International Dialogues on Education Journal, 2023)
Covid-19 has affected the world, and its impact is not limited to medical and health aspects. It has also affected social, educational, business, economic, and work environments. The spread of the virus has forced most companies to implement work-from-home (WFH) policies to reduce the mobility of employees and curb the virus's spread, despite potential adverse effects on employees' productivity and performance. This research aims to rank the criteria for improving employees' productivity during WFH using the Fuzzy- method. Four criteria and eight sub-criteria were identified to promote employees' productivity. The four main criteria are Income, Work Schedule, Work Environment, and Work Partner. Data processing results show that these criteria rank from top to bottom as follows: Work Schedule, Work Environment, Work Partner, and Income. We hope that the rankings observed in this research will help managers set policies to increase their employees' productivity when working from home.